(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2016)
With the tremendous and broadly scattered populace of India it has dependably been a test for organizations to control market progress and they need to strive to make their vicinity felt all through the length and expansiveness of the country. Gone are the days when an insignificant promotion on radio or an imaginative publicizing battle was sufficient to hypnotize the objective client. Today digital consumer is articulate and demanding driving global conversations on every product and service influencing brand image and bottom line like never before. a comprehensive digital marketing solution that helps engage with consumer, influence their opinions, provide relevant feedback, reach various demographics and glean actionable insights- thus become critical to successful corporate strategy. The developing web entrance, the high offers of advanced mobile phones and the 3G administrations being generally made accessible by cell telephone organizations in India together make impeccable conditions for a computerized upset to occur. What’s more, this is going on the grounds that if in today’s age an organization or brand “is out of site it goes out of psyche”, consequently promoting has turned into a fundamental malice. The advertising arrangement essentially means to make the business furnish the arrangement with the mindfulness with the normal clients. From 1980 onward, on the other hand, the Indian state has moved Indian political economy towards East Asian models of improvement. This paper aims to know the scope of digital marketing in India, its trends and future growth.